Canada-Wheat : Discrimination, Non-Commercial Considerations, And State Trading Enterprises - Hoekman, Bernard M. 1959- (The World Bank, 2007)
Statutory marketing boards that have exclusive authority to purchase domestic production, sell for export, and set purchase and sales prices of commodities are a type of state trading enterprise that is subject to World Trade Organization disciplines. This paper assesses a recent dispute brought by the United States against Canada, alleging that WTO rules require state trading enterprises to operate solely in accordance with commercial considerations and that the Canadian government did not require the Canadian Wheat Board to do so. The panel and Appellate Body found that the primary discipline of the WTO regarding state trading enterprises was nondiscrimination, and that operating on the basis of "commercial considerations" was not an independent obligation. Instead, WTO disciplines regarding the pricing behavior of state trading enterprises use a "commercial considerations" test as a possible indicator of discrimination. Although a significant degree of price discrimination is observed in the case of Canadian wheat exports, there are economic arguments why this might also be pursued by a private, profit maximizing firm